EFEKTIFITAS PENERAPAN BLENDED LEARNING DALAM UPAYA MENINGKATKAN KEMAMPUAN AKADEMIK MAHASISWA MELALUI JEJARING SCHOOLOGY DI MASA PANDEMI COVID-19 - Tabah Heri Setiawan; Aden Aden (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
The Covid-19 pandemic makes the learning/lecturing process carried out online to break the chain of spreading the coronavirus. One of the models that can be applied to online learning is blended learning by combining LMS and video conferences. The purpose of this study was to see how effective the use of blended learning is in improving student academic abilities through Schoology during the COVID-19 pandemic. The research design used the Non-Equivalent Control Group Design for 2 treatments (cycles), before and after the midterm exam. Techniques for data analysis using Normality-Gain Test (N-gain) and T-Test for two groups of independent samples. The N-gain value in the experimental class was 43.57% in the medium category, while in the control class the N-gain value was 4.55% in the low category. Based on the results of the t-test, it was obtained that the t-count value was 8.8367 and the t-table value was 2.030, because t-count > t-table there was a significant difference between the experimental class and the control class. So that the application of the blended learning model using Schoology can improve students' academic skills.